Kinetics of epoxidized oleic acid derived from palm oil by in situ generated performic acid - Jalil, Mohd Jumain (Array, 2019)
Epoxidized palm oleic acid is often regarded as a highly valuable oleochemical due to its wide range of industrial applications, including cosmetics, personal care, and pharmaceutical products. In this study, oleic acid derived from palm oil with iodine value of 98.99 g/100 g, containing 75 % of oleic acid, 12 % of linoleic acid, 6.5 % of palmitic acid, and 6.5 % of stearic acid was epoxidised by in situ generated performic acid with hydrogen peroxide as oxygen donor and formic acid as active oxygen carrier in the presence of catalytic amount of inorganic acid. The rate constant for epoxidation of oleic acid was found to be 1.133 ∙ 10–3 mol–1 s–1 and activation energy was 91.12 kJ mol–1 at temperature of 75 °C. In addition, thermodynamic parameters such as enthalpy, entropy, and free energy of activation were 88.2 kJ mol–1, −67.90 J mol–1 K–1, and 88.36 kJ mol–1, respectively. Relative conversion data showed that it was possible to develop epoxides from locally available, natural, renewable resources such as palm oil.